Vulnerability and Housing Policies through the Lens of Anthropology. An Introduction - Giacomo Pozzi; Rita Ávila Cachado; Ana Luísa Micaelo (Archivio Antropologico Mediterraneo)
The Dossier «Vulnerability and Housing Policies. Anthropological insights across Europe» is the result of a panel organized by the editors at the 15th EASA Biennial Conference hosted by Stockholm University in August 2018. In this context, we proposed to explore ethnographically housing policies as peculiar and paradigmatic forms of contemporary «regimes of mobility». Coherently to the panel target, the main theme of this Dossier is the anthropological analysis of the production of social and political vulnerability in Europe through housing policies. In particular, the ethnographies hosted in this Dossier explore the dense intersection between different configurations of social and political action, such as housing rights, residents’ responses to public policies, vulnerability, real estate politics, migration, forced evictions, infrastructures. It is impossible to understand contemporary Europe, we argue, without understanding what is going on with housing policies. Anthropology may give a fundamental contribution in this sense.